Patient-Centered Outcomes and Key Study Procedure Finalization in the Pilot Feasibility Gout Randomized Trial: Comparative Feasibility Study in GOUt, CHerry Extract Versus Diet Modification (Mini-GOUCH). Issue 5 (August 2020) - Singh, Jasvinder A.; Willig, Amanda L.; Darnell, Betty; Green, Candace; Morgan, Sarah; Weiss, Rick; Saag, Kenneth G.; Cutter, Gary; McGwin, Gerald
Abstract : Objective: The aim of this study was to report patient-centered outcomes and finalization of key study procedures from a 9-month pilot internet randomized controlled trial of cherry extract versus diet modification. Methods: We randomized 84 people with physician-confirmed gout in an internet study to cherry extract (n = 41) or dietitian-assisted diet modification for gout (n = 43). All study outcomes were collected via internet and phone calls. We finalized key study procedures. We assessed acceptability and feasibility of the intervention and satisfaction with study website. Results: Study participant satisfaction with the intervention was high. The intervention was perceived as easy, enjoyable, understandable, and helpful (scores 65–88 for all; higher = better). The amount of time spent for the study was acceptable. Participant satisfaction with website interaction and content was very high; 85% or more were moderately to extremely satisfied. Significantly lower total calories, total carbohydrate, and saturated fat intake were noted at 6 months in the diet modification versus cherry extract group; differences were insignificant at 9 months. Six of the 8 Health Assessment Questionnaire sections/domains improved significantly from baseline to 9 months in cherry extract versus 2 Health Assessment Questionnaire sections/domains in the diet modification group. Key study procedures were finalized for a future trial, including an internet diet assessment tool, gout flare assessment, provider confirmation of gout diagnosis, patient reporting of classification criteria, and centralized laboratory-assisted serum urate testing. Conclusions: High patient acceptability and feasibility of study/intervention and finalization of key study procedures indicate that hypothesis-testing internet gout trials of cherry extract and/or diet modification can be conducted in the future. Abstract : In this preliminary study, the authors sought to determine the feasibility of conducting an intervention for the treatment of gout. The aim of the study was to determine acceptability and feasibility as a preliminary step to the conduct of the trial itself in patients with gout (n = 84). Indeed, the results of thos preliminary study were reassuring and thus the actual trial could take place.Supplemental digital content is available in the text.